Spinocerebellar ataxia type 6 in Brazil Ataxia espinocerebelar tipo 6 no Brasil - Hélio A.G. Teive; Renato Puppi Munhoz; Salmo Raskin; Lineu César Werneck (Arquivos de Neuro-Psiquiatria, 2008)
Spinocerebellar ataxia type 6 (SCA 6) is an autosomal dominant cerebellar ataxia caused by CAG repeat expansion in the SCA6 gene, a alpha 1A voltage-dependent calcium channel subunit gene on chromosome 19p13. SCA-6 is characterized predominantly by slowly progressive pure cerebellar ataxia with late onset. We report three index patients, with pure, late onset, cerebellar ataxia, belonging to three different Brazilian families, all of them with Japanese ancestry, from Hokkaido island of Japan. Ataxia espinocerebelar tipo 6 (AEC6) é uma ataxia cerebelar autossômica dominante causada por uma expansão repetida do tripleto CAG no gene da AEC, que é uma sub-unidade do canal de cálcio voltagem-dependente alfa1A localizada no cromossomo 19p13. A AEC6 é caracterizada predominantemente por quadro de ataxia cerebelar pura, com início tardio, e evolução lentamente progressiva. Relatamos três pacientes índices, com ataxia cerebelar pura, de início tardio, pertencentes a três diferentes famílias brasileiras, todas com ancestrais japoneses, oriundas da ilha de Hokkaido.